Tinjauan Yuridis Terhadap Kewenangan Kementrian Energi Sumber Daya Mineral Dalam Pelaksanaan Izin Usaha Pertambangan Dikaitkan Dengan Pemanfaatan Mineral Ikutan Berdasarkan Perundang-Undangan Pertambangan di Indonesia Dikaitkan Dengan Asas Manfaat - Raissa Hamdani, Kirana; Andersen, Christian (Universitas Ekasakti, 2024)
Indonesia is a country with abundant natural resources, especially minerals and coal. The country is among the top 10 largest mining producers in the world. Mineral mining activities, both metal and non-metal, generally produce main minerals and associated minerals. However, the important thing that needs to exist in the granting of mining business licenses is based on the mining object or based on the mining process area. This is what is disputed or ambiguous, especially compared to legislation starting from the law and its derivative regulations. According to article 2 letter e of Law Number 32 of 2009 concerning Environmental Protection and Management, Indonesia's environment must be protected and managed properly based on 14 (fourteen) principles, one of which is the principle of benefit. When associated with the principle of benefits, associated minerals can be a source of benefits because they become a new source of income for local communities. Based on Law 3 of 2020, 10% (ten percent) of the net profit of mining sales in business entities that have a Special Mining Business License (IUPK) is the right of the government, with details of 4% (four percent) for the central government and 6% (six percent) given to local governments. This research uses a type of normative legal research method that focuses on positive law and interviews.